Cover Feature: Synthetic Lubricants Derived from Plastic Waste and their Tribological Performance (ChemSusChem 19/2021). Issue 19 (15th September 2021) - Hackler, Ryan A.; Vyavhare, Kimaya; Kennedy, Robert M.; Celik, Gokhan; Kanbur, Uddhav; Griffin, Philip J.; Sadow, Aaron D.; Zang, Guiyan; Elgowainy, Amgad; Sun, Pingping; Poeppelmeier, Kenneth R.; Erdemir, Ali; et al.
Abstract : The Cover Feature shows a mixed waste plastic stream being converted to synthetic motor oil lubricants. A Pt nanoparticle catalyst utilizes H2 gas to selectively break up the hydrocarbon chains via C−C scissions to produce a liquid, monodisperse product. More information can be found in the Full Paper by R. A. Hackler et al .